Peningkatan Prestasi Belajar Bahasa Jawa Materi Tembang Gambuh Menggunakan Strategi Demonstrasi Berbantu Media Berbasis Audio-Visual di Kelas IV SDN 2 Somawangi - Imelda Anom Mulatingtyas; Okto Wijayanti; Sri Harmianto (Universitas PGRI Semarang, 2019)
This study was focused on improving Javanese Language learning achievement of gambuh song material using demonstration strategy audio-visual media based at the fourth grade of SD N 2 Somawangi, which were 21 students that consisted of 10 male students and 11 female students. This study was a Classroom Action Research or PTK conducted in 2 cycles and in each cycle consists of 2 meetings. Each cycle includes planning, action, observation, and reflection. Student achievement data was obtained from the evaluation sheet distributed at each meeting. The improving results can be seen in each cycle. The indicator of the success of this study was an increase in learning outcomes of at least >80% included in the good criteria from the number of students who passed the minimum criteria of mastery learning (KKM) in Javanese Language subjects, it was 65. Learning completeness in the first cycle was 73%. Learning completeness in cycle II was 92% so that from cycle I to cycle II it increased 19%. The conclusion in this study was that Javanese language learning using demonstration strategy audio-visual media based was able to improve student learning achievement in Gambuh song material.